Exophiala dermatitidis isolates from various sources: using alternative invertebrate host organisms (Caenorhabditis elegans and Galleria mellonella) to determine virulence - Olsowski, Maike (Sci Rep, 2018)
Exophiala dermatitidis causes chromoblastomycosis, phaeohyphomycosis and fatal infections of the central nervous system of patients with Asian background. It is also found in respiratory secretions from cystic fibrosis (CF) patients. In this study a variety of E. dermatitidis strains (isolates from Asia, environmental and CF) were characterized in their pathogenicity by survival analyzes using two different invertebrate host organisms, Caenorhabditis elegans and Galleria mellonella. Furthermore, the morphological development of hyphal formation was analyzed. E. dermatitidis exhibited pathogenicity in C. elegans. The virulence varied in a strain-dependent manner, but the nematodes were a limited model to study hyphal formation. Analysis of a melanin-deficient mutant (Mel-3) indicates that melanin plays a role during virulence processes in C. elegans. The strains isolated from Asian patients exhibited significantly higher virulence in G. mellonella compared to strains from other sources. Histological analyzes also revealed a higher potential of invasive hyphal growth in strains isolated from Asian patients. Interestingly, no significant difference was found in virulence between the Mel-3 mutant and their wild type counterpart during infection in G. mellonella. In conclusion, invasive hyphal formation of E. dermatitidis was associated with increased virulence. This work is the basis for future studies concerning E. dermatitidis virulence.